2003
DOI: 10.1038/nature01355
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 rather than interleukin-12 is the critical cytokine for autoimmune inflammation of the brain

Abstract: Interleukin-12 (IL-12) is a heterodimeric molecule composed of p35 and p40 subunits. Analyses in vitro have defined IL-12 as an important factor for the differentiation of naive T cells into T-helper type 1 CD4+ lymphocytes secreting interferon-gamma (refs 1, 2). Similarly, numerous studies have concluded that IL-12 is essential for T-cell-dependent immune and inflammatory responses in vivo, primarily through the use of IL-12 p40 gene-targeted mice and neutralizing antibodies against p40. The cytokine IL-23, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

67
2,152
6
32

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 2,603 publications
(2,275 citation statements)
references
References 30 publications
67
2,152
6
32
Order By: Relevance
“…Moreover, IL-23 is an essential factor in the survival and expansion of Th17 cells [5], which produce cytokines including IL-17, IL-17F, IL-22, IL-6 and TNF-a [6]. p19-deficient mice are highly resistant to the development of experimental allergic encephalomyelitis (EAE) [7], and it has been shown that the IL-23-dependent production of IL-17, but not IL-22 [8], is important for the pathogenesis of autoimmune diseases such as EAE [9]. Recent studies have also revealed that the IL-23-dependent production of IL-22, but not IL-17, plays a critical role in protection against subsequent infection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, IL-23 is an essential factor in the survival and expansion of Th17 cells [5], which produce cytokines including IL-17, IL-17F, IL-22, IL-6 and TNF-a [6]. p19-deficient mice are highly resistant to the development of experimental allergic encephalomyelitis (EAE) [7], and it has been shown that the IL-23-dependent production of IL-17, but not IL-22 [8], is important for the pathogenesis of autoimmune diseases such as EAE [9]. Recent studies have also revealed that the IL-23-dependent production of IL-22, but not IL-17, plays a critical role in protection against subsequent infection.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IL-23 is an essential factor in the survival and expansion of Th17 cells [5], which produce cytokines including IL-17, IL-17F, . p19-deficient mice are highly resistant to the development of experimental allergic encephalomyelitis (EAE) [7], and it has been shown that the IL-23-dependent production of IL-17, but not , is important for the pathogenesis of autoimmune …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon maturation, they then secrete cytokines such as IL-12 and IL-23 that regulate inflammation. In particular, IL-23 is a potent inflammatory cytokine which plays a crucial role in the inflammation of the brain (Cua et al, 2003). The expression of the specific IL-23p19 subunit in transgenic mice also results in systemic inflammation (Wiekowski et al, 2001).…”
Section: -Discussionmentioning
confidence: 99%
“…In 1995 Dr Sakaguchi60, 61 discovered another specific subpopulation of T cells, named regulatory T (Treg) cells, that were specialized for immunosuppression. More recently other subsets have been isolated named Th17 (2005),62, 63 Th9 (2008)64, 65 and Th22 (2009) 40. Finally, single‐cell RNA ‐sequencing has revealed the existence of a subpopulation of steroid‐producing cells within the Th2 compartment 23…”
Section: Introductionmentioning
confidence: 99%